Report of a Case of Hypodontia due to Ectodermal Dysplasia: Early Rehabilitation with Overdenture - Mohajerfar, Maryam; Zarrati, Simindokht; Memari, Yeganeh (Journal of Dental School, 2019)
Alveolar ridge is underdeveloped in ectodermal dysplasia (ED). The available treatment plans include fixed, removable or implant-supported prostheses, alone or in combination. A 5 year-old boy was referred for treatment to the Department of Prosthodontics, Tehran University of Medical Sciences with the chief complaint of missing teeth. Prosthodontic treatment was performed to improve mastication, esthetics, phonetics, and psychological support. Altering the alveolar height also provided a more pleasant musculocutaneous profile. Series of overdentures were fabricated in the same conventional manner to compensate for the patient’s growth. Early treatment had a major impact on self-esteem, masticatory function, speech and facial esthetics of our patient. However, long-term success depends on regular recall appointments.